A detailed study of the Fe-doped TiO2thin films induced by pulsed deposition route - Meng, L. (2018)
Fe-doped TiO2 thin films are deposited on the (100)oriented Si and glass substrates by pulsed laser deposition technique using Fe powder doped TiO2 ceramic target. The structural and optical properties of the film have been studied in detail. The degree of film crystallinity is investigated by X-ray diffraction and confirmed by Raman scattering measurements. The stoichiometry and chemical states of Fe, Ti and O are probed by X-ray photoelectron spectroscopy. The surface morphologies are observed by Scanning electron microscopy. The optical properties are studied by measuring the transmittance and the optical constants, the refractive index and the extinction coefficient. It is found that the substrate temperature is a key factor in determining the thin film structure which further influences the refractive index and the optical band gap of the film. An anatase structure emerges above 300ºC while the rutile structure appears when the substrate temperature is higher than 500ºC. Another result is that Fe exists in the deposited films as Fe3+ and the atomic concentration in the films is much lower than that in the source target.